Entry-Level Employment in Intercollegiate Athletic Departments: Non-Readily Observables and Readily Oberservable Attributes of Job Candidates - Gonzalo Bravo; Doyeon Won; David J. Shonk (Journal of Applied Sports Management, 2013)
Human resource management scholars and practitioners have recognized the importance of understanding the complexities of staffing personnel. This study focused on the perceived importance of attributes for entry-level applicants to collegiate athletic departments. A total of 315 NCAA athletic administrators who were randomly selected responded to a web-based survey. Respondents were asked to rate the importance of 10 easily observable attributes during the screening process, and 10 non-readily observable skills during the hiring process. Results indicated that career-related work experience was considered to be most important during the screening, followed by the applicant’s recommendation, and leadership experience. While in the hiring stage, work ethic, communications skills and motivation were considered the most important attributes. This study adds to the literature in human resource management and athletic administration and has practical implications for prospective employees, athletic administrators and sport management faculty members.
Keywords: Screening; Hiring; Observable; Non-Observable; Job Attributes; Collegiate Athletic Departments